A PDA-BN@MoS2 composite material as a high temperature resistant lubricant additive for titanium alloy extrusion and its application

By using the lubricating coating prepared by PDA-BN@MoS2 composite material, the problem of difficulty in lubrication at high temperature during titanium alloy extrusion processing is solved, efficient lubrication and surface quality improvement are achieved, and it is suitable for industrial applications.

CN116790307BActive Publication Date: 2025-03-18XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310751120.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2025-03-18
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

During the extrusion processing, titanium alloys are unable to effectively lubricate the traditional lubricating medium, causing adhesive molds and surface defects. The traditional methods are complex and dangerous to operate, making them difficult to apply on a large scale.

Method used

The PDA-BN@MoS2 composite material is used as the high-temperature resistant lubricant additive for titanium alloy extrusion, and is prepared by ultrasonic dispersion and magnetic stirring to form a lubricating coating that is easy to clean, chemically stable and has excellent lubricating properties.

Benefits of technology

It realizes effective lubrication of the surface of titanium alloy at high temperature, reduces friction coefficient, reduces defects on the surface of the extruded parts, improves surface quality, and is simple and safe to operate, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116790307B_ABST
    Figure CN116790307B_ABST
Patent Text Reader

Abstract

The present invention discloses a PDA-BN@MoS2 composite material as a high-temperature resistant lubricant additive for titanium alloy extrusion and its application. The present invention uses a slurry method to prepare the PDA-BN@MoS2 composite material, by fully reacting hexagonal boron nitride with dopamine hydrochloride and tris-HCl, so that the surface of the hexagonal boron nitride is covered with a layer of polydopamine, and then mixed with molybdenum disulfide, and the hexagonal boron nitride and molybdenum disulfide are self-assembled by the action of polydopamine to obtain a new type of flaky PDA-BN@MoS2 composite material, the PDA-BN@MoS2 composite material reduces the friction coefficient of hexagonal boron nitride at high temperature, and the lubricating coating prepared by the composite material is easy to fall off from the titanium alloy profile substrate, which is convenient for cleaning the surface of the substrate after the extrusion process is completed. The influence on the base material is very small, and there is a better application prospect in industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lubricant preparation, and in particular relates to a PDA-BN@MoS2 composite material as a high-temperature resistant lubricant additive for titanium alloy extrusion and an application thereof. Background Art

[0002] Titanium alloys have excellent properties such as heat resistance, corrosion resistance and high strength, and are widely used in aerospace, military and other fields. However, my country is currently unable to mass-produce high-quality titanium materials, mainly because the temperature of titanium alloys during the extrusion process is high, the deformation resistance during extrusion is large, and it is easy to stick to the mold. Traditional lubricating media cannot achieve high-precision lubrication, so lubrication treatment is currently a pain point in the process of titanium alloy extrusion processing.

[0003] Traditional solid lubricant coatings are made of materials such as graphite, molybdenum disulfide, and polytetrafluoroethylene. However, graphite is easily oxidized and can only be used in forging processes at relatively low temperatures. The working environment is relatively poor, which is harmful to the health of workers. The thermal stability of molybdenum disulfide and polytetrafluoroethylene at high temperatures is not good enough. Titanium alloy extrusion processing must be carried out at high temperatures above 600°C, and traditional solid lubricant materials cannot meet the requirements. Hexagonal boron nitride (h-BN) has a hexagonal lattice layered structure similar to graphite, and has significant thermal stability, good mechanical properties, adsorption properties, high thermal conductivity, low expansion coefficient, good oxidation resistance, and excellent lubrication properties. The existing technology uses hexagonal boron nitride (h-BN) as a lubricating material to obtain a lubricating coating. It is necessary to use laser cladding, chemical vapor deposition (CVD) or high-temperature sintering processes to obtain the lubricating coating. For example, patent CN114774912A discloses a preparation method for in-situ generation of a self-lubricating ceramic high-temperature wear-resistant coating by laser cladding. Although the friction coefficient of the coating is lower than that of the substrate, the coating cannot be directly cleaned and has a certain effect on the substrate material. The lubricating coating obtained by chemical vapor deposition (CVD), high-temperature sintering processes and other methods has a greater impact on the surface of the titanium alloy substrate, and the operation is more complicated, the instrument requirements are higher, the use is also more dangerous, and it is difficult to apply on a large scale.

[0004] In view of the above problems, the present invention aims to provide a lubricant for titanium alloy extrusion which has good chemical stability, lubricity and high temperature resistance and is easy to clean. Summary of the invention

[0005] The first object of the present invention is to provide a PDA-BN@MoS2 composite material as a high-temperature resistant lubricant additive for titanium alloy extrusion, and the second object of the present invention is to provide an application of the PDA-BN@MoS2 composite material.

[0006] The first object of the present invention is achieved in this way. A PDA-BN@MoS2 composite material as a high-temperature resistant lubricant additive for titanium alloy extrusion is prepared by the following method: after ultrasonically dispersing h-BN in distilled water, dopamine hydrochloride and a tris-HCl solution with a concentration of 0.05 mol / L are added, and magnetic stirring is performed at 5-30°C for 10h-24h. After centrifugation, the solid precipitate is washed and dried to obtain PDA-BN; then PDA-BN and MoS2 are added to distilled water for water bath ultrasonic treatment, stirred for 10h-24h and then centrifuged, and the solid precipitate is washed with distilled water and then dried to obtain PDA-BN@MoS2 powder;

[0007] Among them, the mass ratio of h-BN and dopamine hydrochloride is 1:0.4-0.6, the mass volume ratio of h-BN and tris-HCl solution is 1:0.7-0.9 g / ml, and the mass ratio of PDA-BN, MoS2 and distilled water is 1:0.25-0.5:50.

[0008] The second object of the present invention is achieved in that the PDA-BN@MoS2 composite material is used as a lubricant additive in the preparation of high-temperature resistant lubricants and lubricating coatings for titanium alloy extrusion.

[0009] The beneficial effects of the present invention are:

[0010] 1. The present invention uses a slurry method to prepare a PDA-BN@MoS2 composite material, by fully reacting hexagonal boron nitride with dopamine hydrochloride and tris-HCl, so that the surface of the hexagonal boron nitride is covered with a layer of polydopamine, and then mixed with molybdenum disulfide, and the hexagonal boron nitride and molybdenum disulfide are self-assembled by the action of polydopamine to obtain a new sheet-like PDA-BN@MoS2 composite material, which reduces the friction coefficient of hexagonal boron nitride at high temperature, and the lubricating coating prepared by the composite material is easy to fall off from the titanium alloy profile substrate, which is convenient for cleaning the surface of the substrate after the extrusion process. It has little effect on the base material and has better application prospects in industry.

[0011] 2. The present invention uses aluminum hydroxide and phosphoric acid to prepare aluminum dihydrogen phosphate, then adds methyltriethoxysilane, forms a modified binder through water bath ultrasound and magnetic stirring, and adds sodium dodecylbenzenesulfonate / sodium dodecylhexasulfonate dispersant to prepare a lubricating medium with good adhesion and dispersibility, and can maintain good performance in a high temperature environment without failure.

[0012] 3. The lubricating coating for titanium alloy extrusion prepared by the present invention has excellent chemical stability, lubricity and high temperature resistance, can effectively reduce defects such as grooves and cracks on the surface of extruded parts, improve the surface quality of titanium alloys, and has great significance for expanding the application of titanium alloys in aerospace and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Schematic diagram of the preparation process of PDA-BN@MoS2 composite material;

[0014] Figure 2 Reaction schematic diagram for the preparation of PDA-BN@MoS2 composite material;

[0015] Figure 3 Schematic diagram of the preparation process of the modified binder;

[0016] Figure 4 A schematic diagram of the preparation process of a high temperature resistant lubricant for the surface of titanium alloy;

[0017] Figure 5 This is a SEM electron microscope image of the PDA-BN@MoS2 composite material prepared in Example 1;

[0018] Figure 6 This is a SEM electron microscope image of the lubricating coating prepared in Example 1;

[0019] Figure 7 This is a picture of the original state of the titanium alloy solid lubricating coating prepared in Example 1 attached to the titanium alloy substrate;

[0020] Figure 8 This is a friction curve diagram of the lubricating coating prepared in Example 1 after a high temperature friction test at an experimental temperature of 800°C;

[0021] Fig. 9 This is a scanning electron microscope image of the wear scar of the plate after the coating prepared in Example 1 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0022] Fig.10 This is a scanning electron microscope image of the ball wear scar of the coating prepared in Example 1 after a high temperature friction test at an experimental temperature of 800°C;

[0023] Fig.11 The friction curve of the coating prepared in Example 2 after a high temperature friction test at an experimental temperature of 800°C;

[0024] Fig.12 This is a scanning image of the wear scar of a plate after the coating prepared in Example 2 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0025] Fig.13This is a scanning image of the small ball wear scar after the coating prepared in Example 2 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0026] Fig.14 This is a friction curve diagram of the coating prepared in Example 3 after a high temperature friction test at an experimental temperature of 800°C;

[0027] Fig.15 This is a scanning image of the wear scar of a plate after the coating prepared in Example 3 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0028] Fig.16 This is a scanning image of the small ball wear scar after the coating prepared in Example 3 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0029] Fig.17 This is a friction curve diagram of the coating prepared in Example 4 after a high temperature friction test at an experimental temperature of 800°C;

[0030] Fig.18 This is a scanning image of the wear scar of a plate after the coating prepared in Example 4 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0031] Fig.19 This is a scanning image of the small ball wear scar after the coating prepared in Example 4 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0032] Fig. 20 This is a friction curve diagram of the coating prepared in Example 5 after a high temperature friction test at an experimental temperature of 800°C;

[0033] Fig.21 Scanning image of the wear scar of the plate after the coating prepared in Example 5 was subjected to a high temperature friction test at 800°C

[0034] Fig. 22 This is a scanning image of the small ball wear scar after the coating prepared in Example 5 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0035] Fig.23 The friction curve of the coating prepared in Comparative Example 1 after a high temperature friction test at an experimental temperature of 800°C;

[0036] Fig.24 This is a scanning image of the wear scar of a plate after the coating prepared in Comparative Example 1 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0037] Fig.25 This is a scanning image of the small ball wear scar of the coating prepared in Comparative Example 1 after a high temperature friction test at an experimental temperature of 800°C;

[0038] Fig.26The friction curve of the coating prepared in Comparative Example 2 after the high temperature friction test at 800 ℃ experimental temperature;

[0039] Fig. 27 This is a scanning image of the wear scar of a plate after the coating prepared in Comparative Example 2 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0040] Fig.28 This is a scanning image of the small ball wear scar after the coating prepared in Comparative Example 2 was subjected to a high temperature friction test at an experimental temperature of 800°C;

[0041] Fig.29 This is a diagram of the coating prepared in Example 1 after cleaning after the high temperature experiment. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited in any way. Any changes or substitutions made based on the teachings of the present invention belong to the protection scope of the present invention.

[0043] The present invention discloses a PDA-BN@MoS2 composite material as a high-temperature resistant lubricant additive for titanium alloy extrusion. The preparation method thereof is as follows: after ultrasonically dispersing h-BN in distilled water, dopamine hydrochloride and a tris-HCl solution with a concentration of 0.05 mol / L are added, magnetic stirring is performed at 5-30°C for 10h-24h, and solid precipitates are washed and dried after centrifugation to obtain PDA-BN; PDA-BN and MoS2 are then added to distilled water for water bath ultrasonic treatment, stirred for 10h-24h and then centrifuged, and the solid precipitates are washed with distilled water and then dried to obtain PDA-BN@MoS2 powder;

[0044] Among them, the mass ratio of h-BN and dopamine hydrochloride is 1:0.4-0.6, the mass volume ratio of h-BN and tris-HCl solution is 1:0.7-0.9 g / ml, and the mass ratio of PDA-BN, MoS2 and distilled water is 1:0.25-0.5:50.

[0045] The particle size of the h-BN is 1-2µm, and the particle size of the MoS2 is 1-2µm.

[0046] The ultrasonic frequency is 35kHz-40kHz, the ultrasonic time is 30-200min, the centrifugal speed is 5000~7000r / min, and the centrifugal time is 8-10min; the number of cleaning times with distilled water is 3~4 times, the water bath temperature is 40-50℃, the drying temperature is 20-40℃, and the drying time is 20-24h.

[0047] The present invention also provides the use of the PDA-BN@MoS2 composite material as a lubricant additive in the preparation of a high-temperature resistant lubricant for titanium alloy extrusion.

[0048] The preparation method of the high temperature resistant lubricant for titanium alloy extrusion is achieved by the following steps:

[0049] (1) Preparation of modified binder: aluminum hydroxide and phosphoric acid in a mass volume ratio of 1.4:3 g / ml are taken, stirred at 150-200° C. and a speed of 350-400 r / min for 30-45 min using a magnetic stirrer to obtain a colorless transparent solution, and allowed to stand at room temperature to obtain an AP binder, and methyltriethoxysilane is added thereto, stirred at a stirring rate of 350-400 r / min and a temperature of 60-80° C. for 60-240 min to obtain a modified AP binder; wherein the volume ratio of phosphoric acid to methyltriethoxysilane is 3:5;

[0050] (2) Preparation of lubricant: Add 2.5-6 g of the PDA-BN@MoS2 powder and 1.5-3 ml of the modified AP binder obtained in step (1) into distilled water and perform water bath ultrasound for 120-180 min at an ultrasound frequency of 35-40 kHz. Then slowly add 0.1-1 g of dispersant and stir at 60-80°C for 120-180 min to obtain a lubricant with a viscosity of 85-94 cp.

[0051] In step (1), the purity of methyltriethoxysilane is 98%.

[0052] In step (2), the dispersant is sodium dodecylbenzene sulfonate.

[0053] The coating method of the lubricating coating for titanium alloy extrusion is to spray the high temperature resistant lubricant evenly on the titanium alloy substrate with a spray gun, and put it into a vacuum drying box for curing and forming after natural drying to obtain the lubricating coating.

[0054] The spray gun used is a high-pressure airless spray gun, and the vertical distance from the nozzle to the workpiece is 250mm-300mm.

[0055] The curing temperature is 100~200℃ and the curing time is 50~120min.

[0056] Example 1

[0057] Take 10g of hexagonal boron nitride powder and disperse it in 500ml of water by ultrasonic. Then take 5g of dopamine hydrochloride and 8ml of 0.05mol / L Tris-HCl solution, stir in a magnetic stirrer for 24h, and then centrifuge and wash. The solid is placed in a drying oven at 60℃ and dried for 10h to obtain solid A. Take 5g of MoS2 and 10g of solid A and disperse them in 500ml of water by ultrasonic. Stir in a magnetic stirrer for 24h, and centrifuge and dry for 48h to obtain PDA-BN@MoS2 composite material. Figure 5It can be seen that PDA-BN is successfully coated on the MoS2 surface. Compared with single h-BN, this structure makes up for the lack of lubrication effect of h-BN.

[0058] Take 1.4g aluminum hydroxide and 3ml phosphoric acid, stir at 150℃ for 30min to obtain aluminum dihydrogen phosphate viscous binder, then add 5ml methyltriethoxysilane, stir at 30℃ for 400min to obtain modified binder. Take 50ml distilled water, 5g composite material powder, and 2ml modified binder, ultrasonically disperse in distilled water for 180min, slowly add 0.1g sodium dodecylbenzene sulfonate dispersant, then stir at 60℃ for 180min to obtain high-temperature solid lubricant. Figure 6 It can be seen that the distribution of the flaky lubricant is more uniform, indicating that the lubricant prepared by the present invention has good dispersibility and its structure is more dense and uniform.

[0059] The lubricant was applied to the titanium alloy surface by high pressure spraying, and after natural curing, it was cured at 100°C for 120 minutes to obtain a lubricating coating. Figure 7 It can be seen that the lubricating coating is smoothly and evenly attached to the surface of the titanium alloy substrate, and no cracks, gaps or bubbles are generated.

[0060] Example 2

[0061] Take 10g of hexagonal boron nitride powder and disperse it in 500ml of water by ultrasonic. Then take 5g of dopamine hydrochloride and 8ml of 0.05mol / L Tris-HCl solution, stir in a magnetic stirrer for 24h, and then centrifuge and wash. The solid is placed in a drying oven at 60℃ and dried for 10h to obtain solid A. Take 5g of MoS2 and 23g of solid A and disperse them in 500ml of water by ultrasonic. Stir in a magnetic stirrer for 24h, and centrifuge and dry for 48h to obtain PDA-BN@MoS2 composite material. Take 1.4g of aluminum hydroxide and 3ml of phosphoric acid, stir at 150℃ for 30min to obtain aluminum dihydrogen phosphate viscous binder, then add 5ml of methyltriethoxysilane, stir at 60℃ for 180min to obtain modified binder. Take 50 ml of distilled water, 2.5 g of composite material powder, and 1.5 ml of modified binder and ultrasonically disperse them in water for 180 minutes. Slowly add 1 g of sodium dodecylbenzene sulfonate dispersant, then stir at 60 ° C for 180 minutes to obtain a high-temperature solid lubricant. The lubricant is coated on the surface of the titanium alloy by high-pressure spraying. After waiting for natural curing, it is cured at 100 ° C for 120 minutes to obtain a lubricating coating.

[0062] Example 3

[0063] Take 10g of hexagonal boron nitride powder and disperse it in 500ml of water by ultrasonic. Then take 5g of dopamine hydrochloride and 8ml of 0.05mol / L Tris-HCl solution, stir in a magnetic stirrer for 24h, and then centrifuge and wash. The solid is placed in a drying oven at 60℃ and dried for 10h to obtain solid A. Take 5g of MoS2 and 23g of solid A and disperse them in 500ml of water by ultrasonic. Stir in a magnetic stirrer for 24h, and centrifuge and dry for 48h to obtain PDA-BN@MoS2 composite material. Take 1.4g of aluminum hydroxide and 3ml of phosphoric acid, stir at 150℃ for 30min to obtain aluminum dihydrogen phosphate viscous binder, then add 5ml of methyltriethoxysilane, stir at 60℃ for 180min to obtain modified binder. Take 50 ml of distilled water, 6 g of composite material powder, and 3 ml of modified binder and ultrasonically disperse them in water for 180 minutes, slowly add 1 g of sodium dodecylbenzene sulfonate dispersant, then stir at 60 ° C for 180 minutes to obtain a high-temperature solid lubricant, and apply the lubricant on the surface of the titanium alloy by high-pressure spraying. After waiting for natural curing, it is cured at 100 ° C for 120 minutes to obtain a lubricating coating.

[0064] Example 4

[0065] Take 10g of hexagonal boron nitride powder and disperse it in 500ml of water by ultrasonic. Then take 4g of dopamine hydrochloride and 7ml of 0.05mol / L Tris-HCl solution, stir in a magnetic stirrer for 24h, and then centrifuge and wash. Place the solid in a drying oven at 60℃ and dry for 10h to obtain solid A. Take 2.5g of MoS2 and 10g of solid A and disperse them in 500ml of water by ultrasonic. Stir in a magnetic stirrer for 24h, and centrifuge and dry for 48h to obtain PDA-BN@MoS2 composite material. Take 1.4g of aluminum hydroxide and 3ml of phosphoric acid, stir at 150℃ for 30min to obtain aluminum dihydrogen phosphate viscous binder, add 5ml of methyltriethoxysilane, and stir at 60℃ for 240min to obtain modified binder. 50 ml of distilled water, 4 g of composite material powder and 2 ml of modified binder were ultrasonically dispersed in distilled water for 120 min, 0.5 g of sodium dodecylbenzene sulfonate dispersant was slowly added, and then stirred at 60° C. for 180 min to obtain a high-temperature solid lubricant.

[0066] Example 5

[0067] Take 10 parts of hexagonal boron nitride powder and disperse them in 500ml of water by ultrasonic. Then take 6g of dopamine hydrochloride and 9ml of 0.05mol / L Tris-HCl solution, stir in a magnetic stirrer for 24h, and then centrifuge and wash. Place the solid in a drying oven at 60℃ and dry for 10h to obtain solid A. Take 7.5g MoS2 and 10g of solid A and disperse them in 500ml of water by ultrasonic. Stir in a magnetic stirrer for 24h, and centrifuge and dry for 48h to obtain PDA-BN@MoS2 composite material. Take 1.4g of aluminum hydroxide and 3ml of phosphoric acid, stir at 150℃ for 30min to obtain aluminum dihydrogen phosphate viscous binder, add 5ml of methyltriethoxysilane, and stir at 80℃ for 60min to obtain modified binder. 50 ml of distilled water, 3 g of composite material powder and 2 ml of modified binder were ultrasonically dispersed in distilled water for 180 min, 0.1 g of sodium dodecylbenzene sulfonate dispersant was slowly added, and then stirred at 80° C. for 120 min to obtain a high-temperature solid lubricant.

[0068] Comparative Example 1

[0069] The difference from Example 1 is that PDA-BN@MoS2 composite material is not used, but pure hexagonal boron nitride is used as the matrix lubricating material, and the other steps are the same.

[0070] Comparative Example 2

[0071] The difference from Example 1 is that PDA-BN@MoS2 composite material is not used, but PDA-BN material is used as the matrix lubricating material, and the other steps are the same.

[0072] Comparative Example 2

[0073] The difference between Comparative Example 2 and Example 1 is that the binder used is aluminum dihydrogen phosphate, and the other steps are the same.

[0074] Experimental Example 1 High temperature friction test

[0075] The lubricating coatings prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to high temperature friction tests at an experimental temperature of 800°C. The contact form of the friction pair was ball-disc contact. The upper sample was a Si3N4 ball (10 mm in diameter) and the lower sample was a titanium alloy (TC4) disk (50.8 mm in diameter and 6 mm in thickness). The applied load was 20 N, the rotation radius was 15 mm, the speed was 50 mm / s, and the test time was 5 min.

[0076] Result analysis:

[0077] 1. From Figure 8 , Fig.11 , Fig.14 , Fig.17 , Fig. 20It can be seen that the friction curves of the high temperature resistant lubricating coatings prepared in Examples 1-5 measured by a high temperature friction and wear tester (BRUKER UMT) at 800°C are stable, and the average friction coefficients are 0.2685, 0.3280, 0.3854, 0.4031, and 0.4198, respectively, indicating that the high temperature lubricating coatings prepared in the present invention have the ability to reduce friction and reduce energy consumption. Fig.23 and Fig.26 It can be seen that the tribological curves of the lubricating coatings prepared in Comparative Examples 1 and 2 after the high-temperature friction test at 800°C fluctuate greatly and show a continuous upward trend. The maximum friction coefficient of Comparative Example 1 is 0.6094, and the average friction coefficient is 0.54. The maximum friction coefficient of Comparative Example 2 is 0.5469, and the average friction coefficient is 0.5093. The values ​​are greater than the average friction coefficients of Example 1 and Example 2, respectively, and the lubrication effect is poor.

[0078] 2. From Fig. 9 , Fig.12 , Fig.15 , Fig.18 , Fig.21 It can be seen that the wear marks of the high temperature resistant lubricating coatings prepared in Examples 1-5 after the high temperature friction test at 800°C are relatively smooth, without defects such as grooves and cracks, indicating that the high temperature lubricating coatings prepared in the present invention have excellent anti-wear effects, can effectively improve the wear of the titanium alloy substrate, and improve the quality of titanium alloy products. Fig.24 It can be seen that the lubricating coating prepared in Comparative Example 1 has large cavities and a large number of abrasive agglomerates on the wear surface of the plate after the high-temperature friction test at 800°C, indicating that its anti-wear effect is poor. Fig. 27 It can be seen that after the lubricating coating prepared in Comparative Example 2 was subjected to a high-temperature friction test at 800°C, a large amount of wear debris and abrasive agglomerates appeared on the wear scar surface of the plate, indicating that the adhesive had poor viscosity and could not tightly bond the coating and the substrate.

[0079] 3. From Fig.10 , Fig.13 , Fig.16 , Fig.19 , Fig. 22 It can be seen that the diameter of the small ball wear scar of the high temperature resistant lubricating coating prepared in Examples 1-5 after the friction test is small, and the lubricating coating is attached to it, indicating that the lubricating coating forms a transfer film at high temperature and plays a role in protecting the substrate. Fig.25 It can be seen that the lubricating coating prepared in Comparative Example 1 has a relatively serious wear on the ball after the high-temperature friction test at 800°C, the wear scar diameter is relatively large, and no transfer film is formed on the surface, indicating that its wear resistance is relatively poor. Fig.28It can be seen that the lubricating coating prepared in Comparative Example 2 was severely worn after the high-temperature friction test at 800°C, and no transfer film was formed, indicating that its lubrication and anti-wear properties were poor.

[0080] 4. From Figure 7 , Fig.29 It can be seen that after high-temperature lubrication using the lubricant prepared by the present invention, the coating has no surface damage after being cleaned with liquids such as tap water and alcohol, and the coating is easy to fall off.

[0081] In summary, the average friction coefficient of the lubricating coating prepared in Example 1 is reduced by 50% compared with that in Comparative Example 1, and the lubrication effect is obvious, proving that the PDA-BN@MoS2 composite material prepared by the present invention is indeed superior to the traditional hexagonal boron nitride powder in terms of lubrication performance. The average friction coefficient of the lubricating coating prepared in Example 2 is reduced by 47.2% compared with that in Comparative Example 2, and the adhesion of the coating is more superior, indicating that the modified binder helps to enhance the lubrication effect, and the use of the modified binder can reduce the wear scar diameter, reduce the wear rate, and improve the friction reduction and wear reduction performance.

Claims

1. A PDA-BN@MoS2 composite material as a high temperature resistant lubricant additive for titanium alloy extrusion, characterized in that The preparation method is as follows: h-BN is ultrasonically dispersed in distilled water, dopamine hydrochloride and a tris-HCl solution with a concentration of 0.05 mol / L are added, and magnetic stirring is performed at 5-30°C for 10h-24h. After centrifugation, the solid precipitate is washed and dried to obtain PDA-BN; PDA-BN and MoS2 are then added to distilled water for water bath ultrasonic treatment, stirred for 10h-24h and then centrifuged, and the solid precipitate is washed with distilled water and dried to obtain PDA-BN@MoS2 powder; in, The mass ratio of h-BN and dopamine hydrochloride is 1:0.4-0.6, the mass volume ratio of h-BN and tris-HCl solution is 1:0.7-0.9 g / ml, and the mass ratio of PDA-BN, MoS2 and distilled water is 1:0.25-0.5:

50.

2. The PDA-BN@MoS2 composite material according to claim 1, characterized in that: The ultrasonic frequency is 35kHz-40kHz, the ultrasonic time is 30-200min, the centrifugal speed is 5000~7000r / min, and the centrifugal time is 8-10min; the distilled water is used for washing 3~4 times, the water bath is 40-50℃, the drying temperature is 20-40℃, and the drying time is 20-24h.

3. Use of the PDA-BN@MoS2 composite material according to claim 1 as a lubricant additive in the preparation of a high-temperature resistant lubricant for titanium alloy extrusion.

4. The use according to claim 3, characterized in that: The preparation method of the high temperature resistant lubricant for titanium alloy extrusion is achieved by the following steps: (1) Preparation of modified binder: aluminum hydroxide and phosphoric acid in a mass volume ratio of 1.4:3 g / ml are taken, stirred at 150-200° C. and a speed of 350-400 r / min for 30-45 min using a magnetic stirrer to obtain a colorless transparent solution, and allowed to stand at room temperature to obtain an AP binder, and methyltriethoxysilane is added thereto, stirred at a stirring rate of 350-400 r / min and a temperature of 60-80° C. for 60-240 min to obtain a modified AP binder; wherein the volume ratio of phosphoric acid to methyltriethoxysilane is 3:5; (2) Preparation of lubricant: 2.5-6 g of the PDA-BN@MoS2 powder and 1.5-3 ml of the modified The AP adhesive is added to distilled water and subjected to water bath ultrasound for 120-180 minutes at an ultrasound frequency of 35-40 kHz. Then, 0.1-1 g of dispersant is slowly added and stirred at 60-80°C for 120-180 minutes to obtain a lubricant with a viscosity of 85-94 cp.

5. The use according to claim 4, characterized in that: In step (1), the purity of methyltriethoxysilane is 98%.

6. The use according to claim 4, characterized in that: In step (2), the dispersant is sodium dodecylbenzene sulfonate.

7. The use according to claim 3, characterized in that: The coating method of the high temperature resistant lubricant for titanium alloy extrusion is to spray the high temperature resistant lubricant evenly on the titanium alloy substrate with a spray gun, and put it into a vacuum drying oven for curing and forming after natural drying to obtain a lubricating coating.

8. The use according to claim 7, characterized in that: The spray gun used is a high-pressure airless spray gun, and the vertical distance from the nozzle to the workpiece is 250mm-300mm.

9. The use according to claim 7, characterized in that: The curing temperature is 100~200℃ and the curing time is 50~120min.

Citation Information

Patent Citations

  • Dopamine surface modified two-dimensional nano material and preparation method thereof

    CN107216689A

  • Lubricating oil containing surface modified carbon nanomaterials and preparation method thereof

    CN107739643A